Authorship : from Plato to the postmodern : a reader - Burke, Seán (Edinburgh University Press, 1995)
This reader provides a solid theoretical base for all those encountering the 'author' debate for the first time. It presents key readings from the main writers on authorship, including pieces from Plato, Descartes, Shelley, Freud, T. S. Eliot, Sartre, Derrida, Foucault and Borges, and puts the authorship debates into historical context.
Keywords: Authorship; Authorship in literature; kirjoittaminen; kaunokirjallisuus; tekijyys; kirjailijat; luovuus